2017
DOI: 10.1016/j.trf.2017.04.014
|View full text |Cite
|
Sign up to set email alerts
|

Using optical illusions in the shoulder of a cycle path to affect lateral position

Abstract: An important factor in single-sided accidents of older cyclists is that they ride off the cycle path onto the verge. Two experiments were performed to assess the feasibility of using virtual 3D objects in the verge to affect the lateral position of bicyclists. In the first experiment, different virtual objects were placed in the shoulder and 1150 passing bicyclists were observed using a fixed camera. The (standard deviation of the) lateral position and speed in four conditions with virtual objects differing in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…One researcher provided them with additional information about the purpose and the rationale of the experiment, the camera instrumentation, and the route, while the other researcher installed and calibrated the two cameras on the bicycle. The cameras were mounted on the handlebars as described in Westerhuis et al (2017). One camera was aimed forward to record the cyclist's view and the other was aimed downward to measure lateral position (see Figures 1-3).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…One researcher provided them with additional information about the purpose and the rationale of the experiment, the camera instrumentation, and the route, while the other researcher installed and calibrated the two cameras on the bicycle. The cameras were mounted on the handlebars as described in Westerhuis et al (2017). One camera was aimed forward to record the cyclist's view and the other was aimed downward to measure lateral position (see Figures 1-3).…”
Section: Methodsmentioning
confidence: 99%
“…The cameras recorded videos with a resolution of 1280 Â 720 (180 degrees field of view) at 30 frames per second. A measurement tool was used before each bicycle ride to capture the real-world distances in the video (Westerhuis et al 2017). A public-transport (loan) bicycle was also provided in case participants could not bring their own bicycle.…”
Section: Materials and Equipmentmentioning
confidence: 99%
“…Furthermore, it was observed that sharp turns, narrow paths, and interactions in which another cyclist approached or overtook an older cyclist can precede a risky situation as this might result in a course change towards an obstacle or into the verge. The latter observation was used as input for an experimental measure to keep cyclists away from the verge (Westerhuis, Jelijs, Fuermaier, & De Waard, 2017). No serious crashes occurred during the study, although one cyclist had a minor collision with a cyclist coming from the right who illegally rode on the pavement and was occluded from sight.…”
Section: Cycling Behaviourmentioning
confidence: 99%
“…A good option to explore for the future is the use or development of new measurement devices or smart video analysis algorithms, which can enhance faster detection of critical behaviour of bicyclists, similar to the algorithm for critical driver behaviour detection in naturalistic driving studies by Dozza and González (2013). Moreover, measurement accuracy can also be increased by using relative comparisons (within subjects or rides) or individual camera calibration during experimental measurements (as used in Westerhuis, Jelijs, Fuermaier, and De Waard, 2017).…”
Section: Limitations Of the Study Approachmentioning
confidence: 99%
See 1 more Smart Citation